2014
DOI: 10.1117/1.jbo.19.6.066002
|View full text |Cite
|
Sign up to set email alerts
|

Mapping optical fluence variations in highly scattering media by measuring ultrasonically modulated backscattered light

Abstract: Abstract. Knowledge of the local optical fluence in biological tissue is of fundamental importance for biomedical optical techniques to achieve quantification. We report a method to noninvasively measure the local optical fluence in optically inhomogeneous scattering media. The concept is based on two aspects: the local tagging of light using ultrasonic modulation and the photon path reversibility principle. Our method has advantages over known computational-based fluence mapping techniques, for its purely exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…For simplicity, we assumed that the change in the modulation efficiency due to the change in wavelength dependent scattering is negligible. In our previous work, we have shown that the changes in light modulation efficiency of the US due to changes in local scattering are negligible within a biological relevant range of scattering levels [16]. The assumption is, further, justified for the used wavelengths from our results in Fig.…”
supporting
confidence: 63%
“…For simplicity, we assumed that the change in the modulation efficiency due to the change in wavelength dependent scattering is negligible. In our previous work, we have shown that the changes in light modulation efficiency of the US due to changes in local scattering are negligible within a biological relevant range of scattering levels [16]. The assumption is, further, justified for the used wavelengths from our results in Fig.…”
supporting
confidence: 63%
“…Ultrasound modulated optical tomography (UOT) was originally developed to image absorbing objects inside turbid media [13,14], and it has recently found exciting new applications such as focusing light into turbid media [15], measuring optical fluence variations [16,17], and quantification of scattering inhomogeneities [18]. These applications of UOT are mainly motivated by the invention of a heterodyne parallel speckle detection (HPSD) method using a CCD camera [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Photoacoustics (PA) and acousto-optic tomography (AOT) (Resink et al 2012) combine the use of sound and light in turbid media. The combination of PA and AOT measurements makes it possible to perform fluence compensated photoacoustic imaging as shown by Daoudi et al (2012) and Hussain et al (2014). In this approach, the so called ultrasonically modulated or 'tagged' fraction of light plays an important role.…”
Section: Introductionmentioning
confidence: 99%